ضمانات أطراف التحكيم في مواجهة الحكم التحكيمي دراسة في القانون الليبي - المنفي خالد محمد حسن (Tobruk University Journal of Social and Human Sciences, 2023)
The arbitration litigation, although it is similar to the judicial litigation, is certainly not a judicial litigation in the technical sense of the meaning of this word, as the law of pleadings organizes the official judiciary organically and procedurally, but the matter is different in the field of judicial litigation so that the arbitrator is not bound - by origin - only by the procedures agreed upon by the parties, and thus is not subject to the general rules related to the state’s judiciary, as he is an ordinary individual trusted by the litigants entrusted with hearing a specific arbitral dispute, and despite his independence from the state, he participates in the official judge in many manifestations of his powers, And what is issued by it is considered a judicial act in the strict sense, as it addresses the dispute, and separates the litigants with a ruling that obliges the parties to respect and implement it. Thus, the text explicitly stated that the right of the parties to confront the breach issued by the arbitrator was enabled by the possibility of appealing against the arbitral award or filing an action for its invalidity.